The effect of phase angle on crack growth mechanisms under thermo-mechanical fatigue loading. (June 2020) - Jones, J.; Whittaker, M.; Lancaster, R.; Hyde, C.; Rouse, J.; Engel, B.; Pattison, S.; Stekovic, S.; Jackson, C.; Li, H.Y.
Highlights: A comparison of TMF crack growth rates under varying phase angle. A theory of the interaction of fatigue, creep and environment as phase angle varies in TMF crack growth tests. A study of the effects of grain size in TMF crack growth testing. Abstract: The current paper describes TMF crack growth behaviour in an advanced nickel-based superalloy. Changes in behaviour are examined which occur as a function of the phase angle between applied stress and temperature. The fractography of the failed specimens reveals changes from transgranular to intergranular growth between high and low phase angle tests as a result of the onset of high temperature damage mechanisms. More targeted testing has also been undertaken to isolate the contributions of these mechanisms, with specific transitions in behaviour becoming clear in 90° diamond cycles, where dynamic crack growth and oxidation strongly interact.